Identifikasi Jenis Tanaman di Beberapa Jalur Hijau Jalan Kota Medan1 (Identification of Plant Species at a Few Street Green Belt of Medan City) - Hafsah Purwasih; Siti Latifah; Asep Sukmana (Peronema Forestry Science Journal, 2013)
One of the green open space  that enough effective to reduce carbon emission at around the street in town is a green belt. Plants that planting in green belt was good to absorb carbon emission. So its important to knowing the kind of plants there. The aim of this research is to know what kind of plants that planting in green belt. This research have done at 21 green belt in 21 district in Medan city. The sample of belt and plants in belt had taken by purposive sampling and sensus method. And the method of data analysis was doing by identification species. The results showed that finding 33 of species plants at green belt choosen with the species was dominated is Angsana (Pterocarpus indicus). Key words: Green Belt, Identification Plants, Reducing Emissions, Angsana